Відновлення кіральної симетрії з використанням рухомої константи зв’язку в наближенні світлового фронту у КХД - Campos, S.D. (Publishing house "Academperiodika", 2022)
In this work, the distance between a quark-antiquark pair is analyzed through both the confinement potential and the hadronic total cross- section. Using the Helmholtz free energy, the entropy is calculated near the minimum of the total cross-section through the confinement potential. A fitting procedure for the proton-proton total cross- section is carried out, defining the fit parameters. Therefore, the only remaining free parameter in the model is the mass-scale к used to define the running coupling constant of the light-front the approach to QCD. The mass scale controls the distance r between the quark-antiquark pair and, under some conditions, allows the appearance of free quarks even within the confinement regime of QCD.